Surgical Management of a Massive Frontal Bone Hemangioma: Case Report - Bird, Cylaina E.; Traylor, Jeffrey I.; Johnson, Zachary D.; Kim, Jun; Raisanen, Jack; Welch, Babu G.; Abdullah, Kalil G. (Journal of Neurological Surgery Reports, 2022)
Intraosseous hemangiomas are rare, benign tumors that can arise from the calvarium. These lesions often invade the outer table of the skull, but typically spare the inner table and intracranial structures. En bloc surgical resection is the standard treatment for intraosseous hemangiomas. However, a piecemeal resection may be required to safely remove the tumor in cases involving the inner table to protect the underlying brain parenchyma and vascular structures. Proper reconstruction is critical to optimize the cosmetic outcome, and a staged procedure allowing implantation of a custom-made implant can be considered for large lesions involving the forehead. We present a case of a patient with a large frontal intraosseous hemangioma with intradural involvement to highlight the surgical nuances of resection and review the existing literature regarding optimal management of these patients.
Keywords: frontal bone; intraosseous hemangioma; skull; surgical management